Traditional medicinal plants used by tribal communities in Tonk district, Rajasthan - Sharma, Swati; Chakraborty, Dipjyoti (Plant Science Today, 2021)
Rajasthan is the third largest state of India. About 80% of the population live in the villages. The main tribes of Rajasthan are Bhil, Meena, Garasia, Saharia, Damor and Kathoudi. The study area comprises of Tonk district of Rajasthan, India which has seven divisions Deoli, Malpura, Todaraisingh, Uniara, Peeplu, Tonk and Newai. Survey method was followed covering five villages of each division. The data were collected through direct interviews with local people, priests, local physician and gardeners. A detailed questionnaire was designed and written in Hindi for the baseline study following standardised procedures. The tribal communities use plants and plant products in their day to day life, however there is a gap in knowledge in the younger generation. A total of 147 species belonging to 62 vascular plant families are reported. From these 145 species were reported to be used for medicinal applications, 135 species of which were used to treat more than one disease and remaining 8 species were used to treat only one disease. The most widely used plant part is leaves (95 species) and the, most common mode of application is oral (39.65%). The traditional knowledge about the plants can be used to produce to new products for medicinal use, food and fodder.